Strengthening Religious Moderation: applying nine core values in Religious Moderation Village - Muhasim; Zulfikar Muhammad; Ifrohan (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2024)
Religious moderation is a must in a nation that has diversity in various things, especially religion. To support this, the Ministry of Religious Affairs of the Republic of Indonesia launched the Religious Moderation Village program. This program is based on the application of nine values of religious moderation, namely tawasuth (moderation), i'tidal (upright and proportional), tasamukh (tolerance), deliberation, al-ishlakh (improvement), qudwah (leadership/pioneering), muwathonah (love for the country), al-a'naf (non-violence), and i'tiraf al-'urf (friendliness to culture). This study is qualitative descriptive, the research population is the community of Sidodadi village, Gedangan district. Data collection was conducted through in-depth interviews and observation, while data analysis used the Colaizzi approach. The results showed that of the nine values of religious moderation, four values have been implemented well in Sidodadi Village. The results showed that of the nine values of religious moderation, four values have been implemented well in Sidodadi Village, namely tasamukh (tolerance), tawasuth (moderation), muwathonah (love of the country), and i'tiraf al-'urf (friendliness to culture). The other five values, deliberation, al-a'naf (non-violence), i'tidal (upright and proportional), al-ishlakh (improvement), and qudwah (l leadership/pioneering), still face various obstacles in their application. This research provides an overview of the successes and challenges of implementing religious moderation values at the local community level.